Algorithm Applied to SDG13: A Case Study of Ibero-American Countries - Barcellos-Paula, L.; Gil-Lafuente, A.M.; Castro-Rezende, A. (MDPI, 2023)
Scientific studies confirm the existence of a crisis caused by climate change, in which global causes produce local effects. Despite climate agreements, greenhouse gas emissions continue to fall short of targets to limit global warming. There is still a need for comparable data for Sustainable Development Goal (SDG) 13—Climate Action. The motivation of the research is to provide data for decision-making and to propose solutions to address the climate crisis. The article aims to propose a Fuzzy Logic algorithm to evaluate the SDG13 indicators and to deepen the discussion on climate change. The research is applied explanatory with a combined approach (quantitative-qualitative) through modeling, simulation, and case studies. As a result, the OWA operator ranks 10 Ibero-American countries to SDG13, indicating Colombia, Peru, and Cuba in the first positions. The main contributions are the reduction of identified knowledge gaps and proposals for action for policy and decision-makers. A limitation of this study would be the number of participating countries. The authors indicate future lines of research.
Keywords: Greenhouse gas; Climate change; Action (physics); Sustainable development; Global warming; Fuzzy logic; Political science; Computer science; Law; Artificial intelligence; https://purl.org/pe-repo/ocde/ford#5.07.00